DESIGNING AND IMPLEMENTING AN AUTOMATED INFORMATION SYSTEM FOR PRESCHOOL EDUCATIONAL INSTITUTIONS - Nazirjonova Nargizaxon Sobirovna; Adambayev Uchqunbek Erkinovich (TADQIQOTLAR.UZ, 2024)
ABSTRACT: This article explores the design and implementation of an Automated Information System (AIS) tailored specifically for preschool educational institutions. It addresses the growing need for streamlined data management, efficient communication, and improved operational processes in early childhood education settings. Using a comprehensive literature review, theoretical foundations, and practical application, the study presents a step-by-step methodology for developing an AIS. The results from pilot implementation in selected preschools reveal significant improvements in administrative efficiency, data accuracy, and stakeholder satisfaction.